2007
DOI: 10.1562/0031-8655(2003)0770349boasog2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Base Oxidation at 5′ Site of GG Sequence in Double-stranded DNA Induced by UVA in the Presence of Xanthone Analogues: Relationship Between the DNA-damaging Abilities of Photosensitizers and Their HOMO Energies ¶

Abstract: UVA contributes to skin cancer by solar UV light. Photosensitizers are believed to play an important role in UVA carcinogenesis. We investigated the mechanism of DNA damage induced by photoexcited xanthone (XAN) analogues (XAN, thioxanthone [TXAN] and acridone [ACR]), exogenous photosensitizers, and the relationship between the DNA‐damaging abilities and their highest occupied molecular orbital (HOMO) energies. DNA damage by these photosensitizers was examined using 32P‐labeled DNA fragments obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Its formation can be considered as a potential environment hazard, because photoexcited acridine is known to induce DNA damage (Hirakawa et al, 2003). Photoinduced tautomerism of acridone on the surfaces resulted in the formation of 9-hydroxyacridine, its principal product.…”
Section: Discussionmentioning
confidence: 99%
“…Its formation can be considered as a potential environment hazard, because photoexcited acridine is known to induce DNA damage (Hirakawa et al, 2003). Photoinduced tautomerism of acridone on the surfaces resulted in the formation of 9-hydroxyacridine, its principal product.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that the radiation-induced yields of 8-OHG in double-stranded DNA were 20- and twofold higher in DNA compared with those in deoxyguanosine in the presence and absence of oxygen, respectively (34). On the other hand, the formation of 8-OHG after UV irradiation in the presence of various photosensitizers was significantly lower for the single-stranded DNA conformation compared with the double-stranded conformation (35). Such disagreements between existing data can be caused by differences in experimental conditions (e.g., ionizing or UV radiation) that can lead to variations in the relative yields of the stable products from guanine radiolysis.…”
Section: Discussionmentioning
confidence: 97%
“…Of the photosensitizers, xanthone and its derivatives have been extensively examined for UVA-induced DNA damage. 11,12) It has been found that xanthone mediates the photosensitized decomposition of fatty ester hydroperoxides to produce oxyl radicals 13) and hydroxyl radicals, 14,15) but to our knowledge, no study focusing on molecular oxygen-derived radicals has been performed. In this study, we detected hydroxyl radical and clarified the reaction mechanism in a reaction mixture of xanthone under UVA irradiation.…”
Section: 2)mentioning
confidence: 99%